Digital Competency and Its Impact on Academic Achievement among Polytechnic Students - Hashim, Suhaizal; Nurhani Khamis; Nor Azli, Nur Imanina; Che Lah, Noor Hidayah (Online Journal for TVET Practitioners, 2026)
In the era of digital transformation that accelerates the evolution of educational systems, mastery of digital competencies in accounting subjects has become a critical foundation for enhancing the quality of learning and preparing students to meet industry demands. This study aims to examine the relationship between digital competencies in accounting subjects and the academic performance of polytechnic students, specifically within the Commerce Department at Ungku Omar Polytechnic. In line with advancements in digital transformation in education, this research focuses on how proficiency in digital tools such as accounting software (MYOB, QuickBooks), interactive e-learning platforms, and data analysis tools can enhance students’ technical skills and stimulate critical thinking through realistic financial scenario simulations. This quantitative study employs the Integrative Digital Competence Assessment (IDCA) model, which encompasses technological, cognitive, and ethical dimensions, with data collected from 287 students through a questionnaire based on the IDCA constructs. Based on descriptive analysis, most respondents were students in semesters 2 (45.3%) and 4 (39.0%) of the Diploma in Accounting program (73.9%), with 96.2% having experience using technology in learning. Analysis of digital competence using the IDCA model showed the highest achievement in the ethical dimension (mean=4.25, SD=0.51), followed by the cognitive dimension (mean=3.86, SD=0.58) and technology (mean=3.54, SD=0.60). The results of Spearman correlation analysis revealed a weak and non-significant relationship between digital competence and academic performance (r=0.044, p=0.460). The results show that all factors studied were at a high level and had significant relationships with students’ academic performance, thus emphasizing the importance of integrating digital technology into the accounting curriculum to ensure graduates are better prepared to meet current industry requirements. These findings also suggest that other factors such as teaching methods, student motivation, or basic accounting skills may have a greater influence on academic achievement than digital competence alone.